Peran BPSK Dalam Menyelesaikan Sengketa Konsumen - Haryani, Anik Tri; Sarjiyati, Sarjiyati; Purwati, Yuni (Universitas Merdeka Madiun, 2020)
Abstractâ€” The purpose of this study is to analyze and explain the role of BPSK in resolving consumer disputes and analyze the dispute resolution process BPSK. This research used normative juridical approach to the law (statute approach) and the conceptual approach (conceptual approach). The results showed that in the implementation of consumer protection in Indonesia, BPSK is spearheading role in the field to provide protection to consumers who have been harmed. The protection afforded by BPSK to consumers is through the settlement of disputes between consumers and businesses, and also through the inclusion of supervision of any agreement or document that outlines the standard clause. While the dispute settlement process is done for the sake of the stages of the stages are as follows: stage request of the applicant, ie the consumer as plaintiff; pretrial stages, namely the selection of completion method; settlement of disputes based on the decision of the parties, especially mediation, conciliation, arbitration and the decision of the Assembly.Â Keywordsâ€”: Role; BPSK; consumer disputes.